Lead us not into Temptation: On the Proposed Revision of the Our Father. (8th October 2019) - Hewitt, Simon
Abstract: Recently a change to the Italian text of the Pater Noster has been proposed. Motivation for this change centers on worries about the suggestion that God leads us into temptation. This paper argues that these worries issue from a confused picture of the relationship between God and creaturely freedom. More fundamentally, however, the suggestion that these kind of worries ought to precipitate revision of liturgical texts fails to take seriously the nature of the liturgy as prayer, rather than simply a means of communicating information. Drawing on Wittgenstein, the sui generis nature of prayer is laid out before the paper concludes with some comments on the distinctive values of both scholarship and prayer.